Leishmaniasis and AIDS coinfection - Adriana Hozannah; Monica Santos; Anette Chrusciak-Talhari; Carolina Talhari (Sociedade Brasileira de Dermatologia, 2013)
Cutaneous leishmaniasis and HIV coinfection has been reported in Brazil since the initial description of AIDS in the country. We report an HIV-positive patient under antiretroviral treatment who presented with cutaneous leishmaniasis which was successfully treated with meglumine antimoniate.